A Clinical Guide to Pediatric HIV Bridging the Gaps Between Research and Practice - Chenneville, Tiffany; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book examines the impact of pediatric HIV on children, adolescents, and their families. Beginning with an overview of pediatric HIV epidemiology, it traces the medical, psychological, and social dimensions of HIV through the trajectory of childhood and youth. It examines the latest research on a wide range of topics, including treatment adherence, cultural, legal, and ethical issues, and HIV stigma and its reduction. Chapters offer expert recommendations for clinicians working with children with HIV as well as researchers studying pediatric HIV. In addition, the book also discusses daily concerns associated with pediatric HIV, such as disease management, coping, access to services, risk prevention, and health promotion. Topics featured in this book include: The impact of pediatric HIV on families. Psychosocial considerations for children and adolescents with HIV. HIV prevention and intervention in the school setting. HIV disclosure in pediatric populations. How to design effective evidence-based HIV risk-reduction programs for adolescents. A Clinical Guide to Pediatric HIV is a must-have resource for researchers, clinicians, and graduate students in child and school psychology, social work, and public health as well as pediatric medicine, nursing, epidemiology, anthropology, and other related disciplines.
Chapter 1. Epidemiology of Pediatric HIV Infection -- Chapter 2. Medical Implications of HIV among Children and Adolescents -- Chapter 3. Developmental Considerations Children and Youth -- Chapter 4. Psychosocial Considerations for Children and Adolescents with HIV -- Chapter 5. The Impact of Pediatric HIV on Families -- Chapter 6. HIV Prevention and Intervention in the School Setting -- Chapter 7. Antiretroviral Medication Adherence and Disease Management in Pediatric Populations -- Chapter 8. HIV Disclosure in Pediatric Populations: Who, What, When to Tell, and Then What? -- Chapter 9. Goodness-of-Fit Ethics for Practice and Research Involving Children and Adolescents with HIV -- Chapter 10. Cultural Considerations for Pediatric HIV Research and Practice -- Chapter 11. HIV Prevention among Youth: Designing Effective Evidence-Based HIV Risk-Reduction Programs for Adolescents -- Chapter 12. HIV-Related Stigma and Children. .
Keywords: Developmental psychology; Child and School Psychology